Neutrophil-Lymphocyte Ratio value as a predictor of Troponin Elevation in patients with Non-ST Segment Elevation Acute Coronary Syndrome - zunardi, Lutfi hafiz; Anjarwani, Setyasih; Prasetya, Indra; Rahimah, Anna Fuji (Universitas Brawijaya, 2024)
Acute coronary syndrome (ACS) is a prominent contributor to mortality and morbidity on a global scale, consistently ranking within the top five primary causes. Inflammation is one of the many elements that have a role in the pathophysiology of the development and destabilization of plaque atherosclerosis in ACS. Troponin is a component of a biomarker that signals damage to the heart muscle in ACS patients; however, at the present time, not all medical facilities are able to perform troponin testing. An acute myocardial infarction begins with an initial inflammatory process that generates proinflammatory cytokines at the cellular level. This can be evaluated by the NLR through peripheral blood tests. The NLR as an indication of systemic inflammation has been demonstrated to be associated with poor clinical outcomes, an increased risk of complications, and mortality in ACS patients. In addition, several studies showed that the NLR has prognostic value in patients with ACS. The NLR is a mix of inflammatory markers, which can be a predictor of increased troponin in cases of non-ST segment elevation acute coronary syndrome (NSTEACS) in an emergency room.